Advanced direct air capture of CO2 using air conditioning systems: a life cycle assessment - Namra Mir (17017734) (2025)
Rising global temperatures and deteriorating urban air quality underscore the urgent need for effective carbon removal technologies. Direct Air Capture (DAC) offers a promising solution, but its high energy demand raises concerns about overall sustainability. This study evaluates the environmental performance of a novel system that integrates DAC with Heating, Ventilation, and Air Conditioning (HVAC) infrastructure to improve energy efficiency and reduce environmental impact. A cradle-to-gate life cycle assessment (LCA) is conducted based on numerical modeling of the DAC-HVAC system. The integrated system exhibits significantly reduced environmental impacts compared to a standalone DAC unit. For the capture of 1 kg of CO2, the DAC-HVAC system results in 0.206 kg CO2 eq. (climate change), 7.521 × 10−7 kg P eq. (freshwater eutrophication), 7.282 × 10−8 kg CFC-11 eq. (ozone depletion), 8.889 × 10−5 kg PM2.5 eq. (particulate matter formation), and 2.051 × 10−3 m3 (freshwater consumption). Notably, the climate change impact is reduced by 15 %, and HVAC-related emissions are lowered by 42 % through integration. These reductions are attributed to decreased electricity requirements achieved via system synergies. Moreover, a sensitivity analysis on different adsorbents and electricity sources is performed. This research highlights the potential for reducing greenhouse gas emissions while addressing indoor air quality concerns. The findings also emphasize the importance of adsorbent selection in the overall environmental impact of the integrated DAC-HVAC system. Future research should explore comprehensive adsorbent assessments and consider end-of-life stages for a more comprehensive understanding of sustainability implications. Other Information Published in: Thermal Science and Engineering Progress License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.tsep.2025.104223